Direct access to spirocycles by Pd/WingPhos-catalyzed enantioselective cycloaddition of 1,3-enynes - Long Li (Nature Portfolio, 2021)
Spirocycles are traditionally difficult structures to synthesize due to the congested nature of the central atom. Here the authors show a method to synthesize quaternary carbon spirocycles in one step from 1,3-enynes and pyrazolidine-type heterocycles, both relatively unactivated structures, proceeding via palladium catalysis.